Chinese Aesthetics in the Past Two Decades - Jianping, Gao (Acta Orientalia Vilnensia, 2002)
This paper is devoted to the discussion of Chinese aesthetics in the last two decades. In the early 1980s, there was an “aesthetic craze” in China, which endeavoured to develop the autonomy of art by breaking away from the art in the service of politics during the period of Cultural Revolution (1966-1976). This “craze” declined in the late 1980s, when people switched to the study of classic Chinese aesthetics in order to find their own cultural identity. During the early 1990s, when some scholars are interested in cultural studies, aesthetics in its narrow sense disappeared in China. In the late 1990s and the turn of the centuries, there was a sign of the revival of aesthetics. Many aestheticians tried hard to develop their studies in various fields, such as to combine aesthetics with contemporary cultural studies and to follow the new development of Western aesthetics, but, more importantly, to establish a Chinese aesthetics in the context of the development of world aesthetics.